Role of School Students’ Engagement in Digital Resources to Shape Academic Procrastination in Mathematics Learning - Chapai, Krishna Prasad Sharma; Joshi, Dirgha Raj (Journal of Mathematics Education, 2026)
With the advancement of technology, the use of digital devices and engagement in social media technologies are increasing day by day. These technologies have provided many opportunities as well as added a new dimension to procrastination behavior. The present study aims to investigate how school student engagement in digital resource shapes the academic procrastination in mathematics learning. This study adopts a cross-sectional survey research design among 415 secondary level school students. Mean, standard deviation, t-test and one way ANOVA were major statistical techniques applied in this research. The finding reveals that students’ access of digital device, time used on digital device for academic purpose, use of social media and their engagement have significant role in shaping academic procrastination. Further, the findings highlight the students without digital resources tend to experience higher procrastination, likely due to limited access, social comparison, and reduced autonomy. To reduce academic procrastination, the finding suggests increasing access of digital resources and providing proper guidance for use of these tools by high school students.